2022
DOI: 10.1108/jfrc-08-2021-0061
|View full text |Cite
|
Sign up to set email alerts
|

Consumer adoption intention toward FinTech services in a bank-based financial system in Vietnam

Abstract: Purpose This study aims to identify the key factors driving consumer adoption attention toward FinTech services in a bank-based financial system to lay a firm ground for further policy recommendations to promote the dual development of FinTech and the banking industry in Vietnam as well as other emerging economies similar banking system. Design/methodology/approach A technology acceptance model with a data set of 387 observations collected from a thorough research design is used and proceeded with probit reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Several studies examining the obstacles to the adoption and application of FinTech were found in the recent systematic literature analysis [18], most of which focused on the payment sector. Studies have been conducted to evaluate the FinTech phenomenon [19][20][21][22][23][24][25]. They mainly concentrated on particular characteristics that are personal attributes of clients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examining the obstacles to the adoption and application of FinTech were found in the recent systematic literature analysis [18], most of which focused on the payment sector. Studies have been conducted to evaluate the FinTech phenomenon [19][20][21][22][23][24][25]. They mainly concentrated on particular characteristics that are personal attributes of clients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, consumer preferences are changing, as the young generation (digital natives) is rapidly identifying the pros and cons of technology-abled services (Koenig-Lewis et al , 2015). The growth and development of the FinTech service sector will be dominantly shaped by users’ needs, the probable supply capability of FinTech firms and the backing of law and policymakers (Ngo and Nguyen, 2022). Since, it offers new prospects for empowering users by enhancing clarity, shrinking costs, eliminating intermediaries and easing accessibility (Ryu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, small-and mediumsized enterprises are the main job creation drivers on the continent (Adjakou 2021). Governments around the world pay special attention to removing barriers to entrepreneurial initiatives to support development through various policies, especially corporate finance (Ngo and Nguyen 2022). One consideration to address this is through crowdfunding, which has the potential to advance poverty alleviation in Africa and on many other continents in a variety of ways, from efficiently rallying and channelling savings to growing businesses in key industrial sectors and, thereby, reducing the vulnerability of some of the poorest people by bringing people together, namely, those with funding needs and those with savings to invest or donate (Hiller 2017).…”
Section: Introductionmentioning
confidence: 99%